A SUGGESTED PROGRAM OF EDUCATION FOR THE ACCOUNTANT. - Miller, Herman C. (The Accounting Review, 1938)
Abstract The 1937 committee on education of the American Accounting Association undertook the task of developing the details of a program providing 60 hours of technical training for the profession of accountancy. It was intended to correlate this program as nearly as possible with the report of the committee on education of the American Institute of Accountants (AIA). Recognizing the desirability of a flexible program which might be suitable for the various types and conditions of educational institutions, the report of the committee incorporates three separate and distinct programs which should be considered together as one general program with boundary limits established. These are designated as the recommended program, the minimum program and the maximum program. In this connection the terms minimum and maximum are used to indicate the amount of concentration in business and accounting subjects. The report of the committee thus covers a rather broad band of concentration varying from 33 hours to 87 hours out of a total of 120 hours usually required for graduation. The recommended program, in conformity with the report of the AIA committee on education, provides exactly 60 hours of business and accounting concentration.